Catalytic signal amplification using [Fe-III(biuret-amide)]-mesoporous silica nanoparticles: visual cyanide detection - Panda, Chakadola; Dhar, Basab B.; Malvi, Bharmana; Bhattacharjee, Yudhajit; Sen Gupta, Sayam (Chemical Communications, 2013)
Catalytic signal amplification was used for the colorimetric detection of CN- in aqueous media by using the enzyme catalase in tandem with mesoporous silica nanoparticle based synthetic HRP enzyme mimic Fe-MSNs. Signal amplification up to a maximum of eight fold was observed for the reporter ``oxidized TMB'' with respect to the added CN- ion.